2022
DOI: 10.3390/s22239310
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Ground Vibrations Generated by Debris Flows Detected by a Lab-Fabricated Seismometer

Abstract: A lab-fabricated ocean bottom seismometer was modified and deployed terrestrially to detect low-frequency (<10 Hz) ground vibrations produced by debris flows. A frequency–response test of the new seismometer revealed that it can detect seismic signals at frequencies of 0.3–120 Hz. Its seismic ground motion detection ability was investigated by comparing its measurements of seismic signals produced by rockfalls with those of a geophone. Two new seismometers were deployed at the Aiyuzi Stream, Nantou County, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(87 reference statements)
1
3
0
Order By: Relevance
“…12). These results are similar to corresponding frequency variations and flow dynamics seen in other studies (e.g., Lavigne et al 2000;Huang et al 2004Huang et al , 2022.…”
Section: Fig 15supporting
confidence: 91%
See 1 more Smart Citation
“…12). These results are similar to corresponding frequency variations and flow dynamics seen in other studies (e.g., Lavigne et al 2000;Huang et al 2004Huang et al , 2022.…”
Section: Fig 15supporting
confidence: 91%
“…Infrasound generation is often associated with the clashing of large particles at the violent surge front, and the surface turbulence created due to collisions between the flow and the channel boundaries (Chou et al 2007;Kogelnig et al 2014;Schimmel and Hübl 2016). Seismic signals, alternatively, are often influenced by basal friction of the flow in contact with the channel bed (Schimmel and Hübl 2016), but also the collision of large particles at the surge front (Huang et al 2007;Bosa et al 2021;Huang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the fourth-generation synchrotron radiation light source requires monitoring of ground vibration signals in the frequency range of 1–100 Hz near the light source [ 1 ]. Seismometer measurements revealed that seismic signals generated by debris flows can have minimum frequencies as low as 2 Hz [ 2 ]. Over the past two decades, various ground vibration sensors, including hydrophones [ 3 , 4 ], geophones [ 5 , 6 , 7 ], seismographs [ 8 , 9 , 10 ], and fiber optic sensors [ 11 ], have been applied to detect and study ground shaking.…”
Section: Introductionmentioning
confidence: 99%
“…High-frequency geophones are compact and inexpensive, but they are only suitable for detecting local and high-frequency signal components. Limited by the influence of the mechanical structure, the frequencies of such ground vibrations detected using conventional geophones are 10–100 Hz [ 2 ]. It is difficult to detect signals lower than the natural frequency, and because of the damping ratio, the sensitivity is not a stable value over the effective frequency range of the sensor.…”
Section: Introductionmentioning
confidence: 99%